Extracellular Cold-Inducible RNA-Binding Protein and Hemorrhagic Shock: Mechanisms and Therapeutics - Naureen Rashid; Zhijian Hu; Asha Jacob; Ping Wang (Biomedicines)
Hemorrhagic shock is a type of hypovolemic shock and a significant cause of trauma-related death worldwide. The innate immune system has been implicated as a key mediator in developing severe complications after shock. Inflammation from the innate immune system begins at the time of initial insult; however, its activation is exaggerated, resulting in early and late-stage complications. Hypoxia and hypoperfusion lead to the release of molecules that act as danger signals known as damage-associated molecular patterns (DAMPs). DAMPs continue to circulate after shock, resulting in excess inflammation and tissue damage. We recently discovered that cold-inducible RNA-binding protein released into the extracellular space acts as a DAMP. During hemorrhagic shock, hypoperfusion leads to cell necrosis and the release of CIRP into circulation, triggering both systemic inflammation and local tissue damage. In this review, we discuss extracellular cold-inducible RNA-binding protein (eCIRP)’s role in sterile inflammation, as well as its various mechanisms of action. We also share our more newly developed anti-eCIRP agents with the eventual goal of producing drug therapies to mitigate organ damage, reduce mortality, and improve patient outcomes related to hemorrhagic shock. Finally, we suggest that future preclinical studies are required to develop the listed therapeutics for hemorrhagic shock and related conditions. In addition, we emphasize on the challenges to the translational phase and caution that the therapy should allow the immune system to continue to function well against secondary infections during hospitalization.